Analysis of selected procedures associated with parceling out of land acquired by virtue of law - Trembecka, Anna (Budownictwo i Architektura / Civil and Architectural Engineering, 2016)
The basic criterion allowing for the subdivision of real estate other than agricultural or forest land is compliance of the planned subdivision with the local plan or, in the absence of a plan, with the provisions of the zoning permit. Regardless of the mentioned planning documents, the subdivision may be carried out for specific purposes. One of them is parceling out of land whose ownership or perpetual usufruct have been acquired by virtue of law.This article aims to present and analyze the cases in which we deal with the acquisition of land by virtue of law, which justifies a subdivision of property, regardless of the planning criteria. The subdivision aimed at parceling out land whose ownership or perpetual usufruct have been acquired by virtue of law applies to such cases in which the legislature has legally parceled out a new property by specifying the entity who has acquired the rights to a part of the property, but there is a need to define boundaries of the acquisition. The examples include proceedings relating to the acquisition of land ownership occupied on 1 January 1999 by public bodies for public roads, municipalization of State property, the purchase of perpetual usufruct of land and ownership of buildings as of December 1990 by state and municipal legal persons having the right of management (the so-called “enfranchisement”), regulating the legal title to land by the PKP (Polish Railroads) company. The paper presents the basis for the acquisition of real estate by virtue of law, the conditions, scope and authorized entities. In practice, subdivisions of real estate are frequently carried out, regardless of the planning decisions, in order to regulate the legal status of land seized in the past for public roads. Therefore, special attention was paid to these issues. Basing on the research, the scope of the documentation for regulating the legal status of the land seized in the past for roads, the number of the issued decisions determining the acquisition of real estate by the Municipality of Krakow and the State Treasury in the analyzed period, and the determined amount of the compensation for the owners, were determined. The research material included the legal provisions, judicial decisions, the study conducted on the property of the Municipality of Krakow.